2015
DOI: 10.1152/ajplung.00243.2014
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced proliferation of tissue-resident endothelial progenitor cells in the lung

Abstract: Exposure to hypoxia induces changes in the structure and functional phenotypes of the cells composing the pulmonary vascular wall from larger to most peripheral vessels. Endothelial progenitor cells (EPCs) may be involved in vascular endothelial repair. Resident EPCs with a high proliferative potential are found in the pulmonary microcirculation. However, their potential location, identification, and functional role have not been clearly established. We investigated whether resident EPCs or bone marrow (BM)-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…The present study revealed that hypoxia induced EPC proliferation. Nishimura et al (23) reported that hypoxia induced the proliferation of tissue-resident EPCs in the lung. Furthermore, Sen et al (22) indicated that exposure to pro-inflammatory cytokines, including angiotensin II, endothelin-1 and tumor necrosis factor, may result in EC dysfunction and the downregulation of S100A1 expression by inducing miR-138 in a manner dependent on the stabilization of HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that hypoxia induced EPC proliferation. Nishimura et al (23) reported that hypoxia induced the proliferation of tissue-resident EPCs in the lung. Furthermore, Sen et al (22) indicated that exposure to pro-inflammatory cytokines, including angiotensin II, endothelin-1 and tumor necrosis factor, may result in EC dysfunction and the downregulation of S100A1 expression by inducing miR-138 in a manner dependent on the stabilization of HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to chronic hypoxia for 21 days resulted in occlusive pulmonary arteriopathy and increased RVSP. The role of hypoxia for promoting proliferation of endothelial precursor cells has been shown previously in the lung 44 . Our results support a concept that the aberrant ECs in PAH occlusive vascular lesions develop by clonal selection from endothelial-like stem cells 4 .…”
Section: Discussionmentioning
confidence: 56%
“…The formation of EC colonies is a feature shared by both EPCs and EC-SP cells; however, we found that EC-SP cells are EC lineagecommitted cells, which do not originate from the bone marrow. In the lung vasculature, the existence of highly proliferative resident progenitor cells that possess an endothelial colony-forming cell (ECFC)-like phenotype has been reported (38,39). ECFCs were originally described in human peripheral and umbilical cord blood based on the timing of their emergence in culture (40).…”
Section: Discussionmentioning
confidence: 99%